STUDI KELAYAKAN USAHA INDUSTRI PEMINDANGAN IKAN DI LINGKUNGAN MAPAK BELATUNG KELURAHAN JEMPONG BARU KECAMATAN SEKARBELA KOTA MATARAM - MARINI, IDA AYU KETUT (GANEC SWARA, 2024)
The potential of fish in Indonesian waters has two seasons, the first is the fishing season which usually occurs between April and November, the lean season occurs between December and March. During the fishing season, fishermen can get catches that exceed the catch capacity for each time they go sailing. The Mapak Belatung Community is a coastal community where most of the population depends on marine products and aquatic animal cultivation, one of which is fish. This is what finally gave birth to fish smoking activities. Unsold fresh fish are processed into pindang fish by fisherwomen in a simple way and then marketed in traditional markets around Mataram City. The purpose of this study was to determine the feasibility of developing a fish smoking industry in the Mapak Belatung Environment, Sekar Bela District, Mataram City when viewed from the investment criteria of Net Present Value (NPV), Net Benefit Cost Ratio (Net B / C), Gross Benefit Cost Ratio (Gross B / C), Profitability Ratio (PR) and Internal Rate of Return (IRR). Based on the calculation of Net Present Value, it shows that the total NPV is Rp. 5,722,264, this means that the palm oil industry business at the research location is feasible to continue because the NPV result is positive (+). The calculation of Net B/C shows that the result is greater than 1 or 1.75, this means that the benefit obtained is 1.75 times the cost or expenses incurred. Based on the calculation of Gross Benefit Cost Ratio, it has a value greater than 1 (> 1), which is 1.233, meaning that the palm oil industry business at the research location is feasible to run, likewise the calculation result of Profitability ratio has a value greater than 1 (> 1), which is 1.97, meaning that the palm oil industry business at the research location is feasible to run. The Internal Rate of Return (IRR) of the palm oil industry at the research location has a value of 17.8 percent or greater than the applicable interest rate